KEPUASAN KONSUMEN TERHADAP MENU DI KUNYIT RESTO PRIME PARK HOTEL PEKANBARU - Devita Rahmadhani; Musadad " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
In the tourism industry especially the hotel sector in Pekanbaru City is a promising business field. The large number of hotels in Pekanbaru makes the management of each hotel compete in providing a good service in order to increase customer satisfaction. In this case Prime Park Hotel Pekanbaru takes into consideration consumer satisfaction in the Food and Beverage Product section in several indicators, specifically appearance, portion, taste and time. Therefore, this study aims to describe how customer satisfaction with the menu at Kunyit Resto Prime Park Hotel Pekanbaru based on several indicators. The data collection technique used in this study was a questionnaire  by consumers at Kunyit Resto Prime Park Hotel Pekanbaru. To test the research, the researchers compiled an experimental field conducted on 100 costumers/ respondents at Kunyit Resto Prime Park Hotel Pekanbaru. After the food and Beverage service is finished, each customer is given a questionnaire consisting of 19 questions to find out their satisfaction. The results showed that consumer satisfaction was very dominant on the taste indicator with the highest percentage count, 96.66%. Keywords: Consumer Satisfaction, F&B Product , Hotel